Comparison of Functional and Radiographic Outcomes of Talar Osteochondral Lesions Repaired With Micronized Allogenic Cartilage Extracellular Matrix and Bone Marrow Aspirate Concentrate vs Microfracture. (July 2021) - Drakos, Mark C.; Eble, Stephanie K.; Cabe, Taylor N.; Patel, Karan; Hansen, Oliver B.; Sofka, Carolyn; Fabricant, Peter D.; Deland, Jonathan T.
Background: Microfracture (MF) has been used historically to treat osteochondral lesions of the talus (OLTs), with favorable outcomes reported in approximately 80% to 85% of cases. However, MF repairs have been shown to degrade over time at long-term follow-up, suggesting that further study into optimal OLT treatment is warranted. The use of adjuvant extracellular matrix with bone marrow aspirate concentrate (ECM-BMAC) has not been extensively evaluated in the literature. We present a comparison of patient-reported and radiographic outcomes following ECM-BMAC repair vs traditional MF. Methods: Patients who underwent MF (n = 67) or ECM-BMAC (n = 62) treatment for an OLT were identified and their charts were retrospectively reviewed. Postoperative magnetic resonance imaging (MRI) was evaluated and patient-reported outcome scores, either Foot and Ankle Outcome Scores (FAOS) or Patient-Reported Measurement Information System (PROMIS) scores, were collected. MRIs were scored by a radiologist, fellowship trained in musculoskeletal radiology, using the Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) system. Radiographic and clinical outcomes were compared between groups. Results: On average, patients treated with ECM-BMAC demonstrated a higher total MOCART score compared to the MF group (73 ± SD 11.5 vs 54.0 ± 24.1; P = .0015). ECM-BMAC patients also had significantly better scores for the Infill, Integration, and Signal MOCART subcategories. Last, patients treated with ECM-BMAC had a lower rate of revision compared to those treated with MF (4.8% vs 20.9%; P = .007). FAOS scores were compared between groups, with no significant differences observed. Conclusion: When comparing outcomes between patients treated for an OLT with ECM-BMAC vs traditional MF, we observed superior MRI results for ECM-BMAC patients. The rate of revision surgery was higher for MF patients, although patient-reported outcomes were similar between groups. The use of ECM-BMAC as an adjuvant therapy in the treatment of OLTs may result in improved reparative tissue when compared to MF. Level of Evidence: Level III, comparative series.